Influence of Multiple Encryptions on the Security and Accuracy of Sent and Received Data - Shareef, Jehan K. (University of Thi-Qar Journal, 2019)
Encryption of data using multiple encryptions has been suggested in a range of contexts and can be used to protect the text versus cryptanalysis. Most work on this topic has intensive on the security of multiple encryptions against plaintext – ciphertext attacks, and has displayed creations secure by merging RC5 and CFB algorithm. This research explains in detail the application which it develops to encrypt and decrypt information depending on RC5 algorithm with the cipher feedback (CFB) mode. RC5 is a block cipher which means the same key will be used for both encryption and decryption. The most commonly chosen is the RC5-32/12/16. Cipher text feedback (CFB) is a mode of operation for a block cipher. This application has both server and client’s side which connect to each other using some ports to exchange encrypted and decrypted data by the RC5 algorithm with CFB mode. Clients connect to server to transmit data in a secure channel. The main aim is to simplify and describe the application which it developed using the RC5 and CFB mode and shows the secure usability of those algorithms.